Comparison between Wordsworth and Robert Frost as a Nature Poet to Develop a Human Behavior: Exploring the Influence of Nature on Human Understanding (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Everyone agrees that William Wordsworth is the greatest poet of Nature. Wordsworth is widelyregarded as one of the greatest philosopher-poets of all time, and his ultimate concern was not onlyNature but the human soul as well. And in the hands of man, poetry advanced as swiftly as Nature's own.Robert Frost, on the other hand, is an excellent poet of both Nature and humanity. All of his sceneriesinclude people in them. Frost once said that he seldom (if ever) wrote a poem that did not include aperson. He has written extensively on a wide range of topics. He has shed light on the natural (a sleepingbird chirping) and the 'mechanistic' (a factory worker's protest) the mundane (a woodpile) and theextraordinary (a Prehistoric pebble). One of literature's most popular recurring topics is the naturalworld. For the Romantics, escaping the bustle of urban life was a cause for rejoicing. On the other side,we can see how modern poets have reworked this theme to highlight the sobering truths and weightyobligations of being human. In this essay, we'll look at how nature poets Wordsworth and Robert Froststack up against one another. It examines the role that nature plays in enriching human understanding. Ahuman knowledge model is the goal of the investigation. The analysts directed the investigation usingin-depth knowledge of nature gained through the application of human cognition, the use of remarkablemedicines to enhance the understanding of human instinct, and the application of high moral standardsin relation to the natural world.